Single-cell and spatial atlas of glioblastoma heterogeneity: characterizing the PCLAF+ subtype and YEATS4’s oncogenic role - Ma, Siqi; Sun, Yuwei; Zheng, Shaowei; Fu, Yilong; Wang, Liangyu; Liu, Dun; Jiao, Henan; Zhu, Xuqiang; Li, Xueyuan; Yan, Dongming; Chen, Di; Ye, Zi (Frontiers in Immunology, 2025)
BackgroundGlioblastoma (GBM) was considered the most aggressive type of primary brain tumor, marked by poor clinical outcomes and a high tendency to relapse. The therapeutic efficacy of GBM was significantly compromised by tumor heterogeneity, dysregulated metabolic pathways, the formation of an immunosuppressive microenvironment, and treatment resistance. Therefore, multi-dimensional therapeutic strategies targeting GBM-specific molecular features, its intrinsic properties, and microenvironmental regulatory networks were considered to potentially provide new breakthroughs for overcoming treatment resistance in GBM.MethodsWe analyzed single-cell RNA sequencing (scRNA-seq) data processed with the Seurat package to accurately identify cell types. Spatial transcriptomics integrated Multimodal Intersection Analysis, TransferData, and Robust Cell Type Decomposition techniques to characterize the spatial distribution patterns of key cell subtypes. CellChat was employed to assess intercellular communication networks. Furthermore, in vitro experiments confirmed the main regulatory role of YEATS4 (key transcription factor of C2 PCLAF+ subtype) in GBM malignant progression.ResultsThrough scRNA-seq, we identified the C2 PCLAF+ subtype in GBM and analyzed its molecular characteristics and functional role in tumor progression. This subtype exhibited a unique malignant phenotype, marked by significant proliferative activity, characteristic metabolic reprogramming, and dysregulated cell death regulation mechanisms. Spatial transcriptomics revealed its preferential localization within specific tumor niches. Furthermore, the C2 PCLAF+ subtype established a specific interaction with fibroblasts through the MDK-LRP1 ligand–receptor pair. Critically, silencing YEATS4 in vitro significantly inhibited GBM malignancy. Additionally, the prognostic risk score model based on the C2 PCLAF+ subtype demonstrated significant clinical translational value.ConclusionOur study systematically elucidated the malignant characteristics of the C2 PCLAF+ subtype and its molecular mechanisms driving GBM progression. This subtype promoted therapeutic resistance through unique metabolic reprogramming, MDK-LRP1-mediated microenvironmental interactions, and immunosuppressive properties. YEATS4 knockdown effectively suppressed malignant tumor behaviors, highlighting its therapeutic potential. These findings provided novel targeted intervention strategies to address GBM heterogeneity and treatment resistance, offering promising avenues for overcoming current therapeutic limitations.